2022
DOI: 10.3390/nu14122549
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Gut Microbial Metabolite Urolithin A on Pancreatic Diseases

Abstract: Urolithin A (Uro A) is a dietary metabolite of the intestinal microbiota following the ingestion of plant-based food ingredients ellagitannins and ellagic acid in mammals. Accumulating studies have reported its multiple potential health benefits in a broad range of diseases, including cardiovascular disease, cancer, cognitive impairment, and diabetes. In particular, Uro A is safe via direct oral administration and is non-genotoxic. The pancreas plays a central role in regulating energy consumption and metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 120 publications
(157 reference statements)
0
16
0
Order By: Relevance
“…Urolithins are the final metabolites of ellagitannins, the main group of hydrolysable tannins [ 13 , 14 , 47 ], which are found in nuts and red fruits, including grapes, pomegranates, and some berries. Ellagitannins are broken down into ellagic acids, which are transformed into urolithins by the action of the gut microbiota [ 14 , 47 , 48 ]. Urolithins are metabolized in enterocytes and hepatocytes into glucuronide, sulfate, and methylated phase II metabolites and are excreted in breast milk and urine [ 13 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urolithins are the final metabolites of ellagitannins, the main group of hydrolysable tannins [ 13 , 14 , 47 ], which are found in nuts and red fruits, including grapes, pomegranates, and some berries. Ellagitannins are broken down into ellagic acids, which are transformed into urolithins by the action of the gut microbiota [ 14 , 47 , 48 ]. Urolithins are metabolized in enterocytes and hepatocytes into glucuronide, sulfate, and methylated phase II metabolites and are excreted in breast milk and urine [ 13 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that higher urinary levels of urolithin B were associated with lower odds of presenting abdominal obesity, which could be attributed to its enhancing effects on thermogenesis, lipolysis, fatty oxidation, and inhibition of lipogenesis and adipogenesis [ 47 ]. Significant interindividual variation has been observed in urolithin production and excretion, with an effect on cardiometabolic health [ 14 , 17 , 18 , 48 ]. Based on urinary excretion, three urolithin metabotypes (UMs) have been identified: UM-A individuals produce only urolithin A, those with UM-B produce urolithin B and isourolithin A, and those with UM-0 are nonproducers [ 14 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…SCFA, as a fuel that can provide energy for epithelial cells, can reduce intestinal pH and inhibit the proliferation of pathogens, thereby improving intestinal barrier and avoiding the translocation of pathogens and antigens [ 72 ].
Figure 2 Scheme of anthocyanin absorption and metabolism [ 75 ]. Anthocyanins can interact with enzymes in the oral cavity after being ingested, resulting in enzymatic hydrolysis of anthocyanins.
…”
Section: Bioavailability Of Anthocyanins and Their Interaction With T...mentioning
confidence: 99%
“…Figure 2. Scheme of anthocyanin absorption and metabolism[75]. Anthocyanins can interact with enzymes in the oral cavity after being ingested, resulting in enzymatic hydrolysis of anthocyanins.…”
mentioning
confidence: 99%
“…In addition, UA inhibits RANKL-induced osteoclast formation and postmenopausal osteoporosis through inhibition of inflammation and downstream NF-κBactivated pyroapoptotic pathway. 25 through protective autophagy. Collectively, these observations confirmed that UA could serve as a promising drug for treating pneumonia.…”
Section: Urolithin a Inhibited Oxidative Stress And Endoplasmic Retic...mentioning
confidence: 99%